The Influence Of Price And Promotion Perceptions On Pinflash Cosmetic Product Purchases Decisions (Survey Of Pinkflash Cosmetics Consumers Using Shopee In Tasikmalaya) - Fitriani, Risna; Lestari, Suci Putri; Asyiah, Ai Kusmiati (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
This research was conducted with the aim of determining the influence of price and promotion perceptions on purchasing decisions (survey of Pinkflash cosmetics consumers using Shopee in Tasikmalaya). The method used in this research is causality through a survey approach, with the sample selected in this research being pinkflash cosmetics consumers using Shopee in Tasikmalaya totaling 100 respondents. The analytical tool used is multiple linear regression with SPSS version 25 tools. The research results show that Price Perception and Promotion have a significant influence on Purchase Decisions for Pinkflash Cosmetic Products in Tasikmalaya. Partially, price perception and promotion have a significant influence on purchasing decisions for Pinkflash cosmetics in Tasikmalaya.